2020
DOI: 10.18280/rcma.303-406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkali Treatment and Dune Sand Content on the Properties of Date Palm Fiber Reinforced Unsaturated Polyester Hybrid Composites

Abstract: The effects of alkali treatment and dune sand (DS) addition on the mechanical, morphological, thermal and water absorption behavior of date palm fiber (DPF) reinforced unsaturated polyester (UP) composites were investigated. The composites were synthesized by hand lay-up method with 10, 20, and 30 wt% of both treated and untreated date palm fiber (TDPF/DPF). Furthermore, composites having 10, 20 and 30 wt% of untreated date palm fiber and dune sand (both of them were in equal wt%) were also fabricated. Alkali … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…Sample B6 containing 6% NaOH treated DPLF fiber showed high tensile strength and elongation at break of 22 MPa and 2.2%, respectively. These results are in accordance with those of Meftah et al [7], regarding tensile strength and flexural strength. Our results confirm also that the tensile strength of our composites has improved by the alkaline treatment of date palm fibers, and this is in accordance with the findings of Rahman et al [18]and Haameem et al [19].…”
Section: B)supporting
confidence: 93%
See 1 more Smart Citation
“…Sample B6 containing 6% NaOH treated DPLF fiber showed high tensile strength and elongation at break of 22 MPa and 2.2%, respectively. These results are in accordance with those of Meftah et al [7], regarding tensile strength and flexural strength. Our results confirm also that the tensile strength of our composites has improved by the alkaline treatment of date palm fibers, and this is in accordance with the findings of Rahman et al [18]and Haameem et al [19].…”
Section: B)supporting
confidence: 93%
“…In the same logic of reflection, Ahmad et al [4][5][6] carried out studies on composites based on epoxy resins and polyesters, looking for the influence of silica nanoparticles (sand) on the mechanical and thermal properties of the composite system. Also, Meftah et al [7] explored the influence of alkaline treatment, and dune sand on the properties of DPLF date palm fiber reinforced with unsaturated polyester by forming hybrid composite systems. On the other hand, one can find in the literature the work effectuated by Alshammari et al [8] based on the manufacture of epoxy resin composites have been carried out by among others mechanical analysis, morphological and physical properties, and water absorption, the fiber is varied like the date palm, palm tree trunk, fruit bunch stalk and leaf stalk.…”
Section: Introductionmentioning
confidence: 99%
“…From the Figure 1, it can be noticed that after adding 10 wt% DPLF in C2, an increase in tensile strength is noticed (3.94% increase), the increase after adding 10% DPLF is in agreement with Meftah et al [7], a 58% improvement has been noticed also in elongation at break of C2.…”
Section: Figure 1 Composites Tensile Strength and Elongation At Breaksupporting
confidence: 86%
“…The thermogravimetric analysis is essential and will show the composites thermal properties over a temperature range indicating how stable the material is. Plenty of scientific articles found in the literature dealt with UPR thermal properties using TGA and showed that UPR thermal degradation is a one step process occurring between 350-420℃ [7], a 2-step degradation process has been reported in some other studies, where the first degradation has been attributed to water molecules evaporation and therefore, it appeared at around 80-120℃. Table 5 summarizes the thermal properties of the analyzed composites.…”
Section: Morphological Propertiesmentioning
confidence: 98%
See 1 more Smart Citation